2021
DOI: 10.3329/bjsir.v56i2.54313
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro plant regeneration from leaf explants of Tagetes erecta L.

Abstract: Regeneration of multiple shoots via callus induction and organogenesis was obtained from young leaf explants of the field grown marigold (Tagetes erecta L.). Callus induction and shoot regeneration at various frequencies were observed using different concentrations and combinations of growth regulators. Highest percentage (90%) of callus formation was observed within two weeks on MS medium supplemented with 5.0 mg/l BAP with 2.5 mg/l NAA. The maximum percentage (80%) of shoot bud formation (10±0.5/callus) was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
1
0
0
Order By: Relevance
“…The T. erecta callus were successfully induced with a combination of BAP and NAA at a concentration of 8 μM, similar to the results of previous studies by Benítez-García et al (2014) and Munshi et al (2021), although Belarmino et al (1992) reported difficulty in regenerating callus from leaf explant. The browning of T. erecta callus in media supplemented with 2, 4-D could be caused by the oxidation of phenolic compounds, leading to cell death (Khosroushahi et al, 2011;Vijayalakhsmi & Shourie, 2017).…”
Section: Discussionsupporting
confidence: 84%
“…The T. erecta callus were successfully induced with a combination of BAP and NAA at a concentration of 8 μM, similar to the results of previous studies by Benítez-García et al (2014) and Munshi et al (2021), although Belarmino et al (1992) reported difficulty in regenerating callus from leaf explant. The browning of T. erecta callus in media supplemented with 2, 4-D could be caused by the oxidation of phenolic compounds, leading to cell death (Khosroushahi et al, 2011;Vijayalakhsmi & Shourie, 2017).…”
Section: Discussionsupporting
confidence: 84%
“…It's a great source of flavonoids, terpenoids, glycosides and tannins, among other classes of bioactive natural compounds [11][12][13]. Numerous antifungal properties of selected plant extracts such as Azadirachta indica, Lantana camara, Moringa oleifera, Wedelia chinensis and Coccinia grandis have outstanding antifungal properties [14][15][16][17][18][19] as well as other numerous properties have been studied [20][21][22][23][24][25][26][27][28][29]. Therefore, the main purpose of this study is to examine the antifungal properties of various plant extracts, Azadirachta indica, Lantana camara, Moringa oleifera, Wedelia chinensis and Coccinia grandis on leather-borne fungi.…”
Section: Introductionmentioning
confidence: 99%